The Sarva-darśana-saṁgraha of Mādhavācārya : with English translation, transliteration, and indices - Mādhava (Chaukhamba Sanskrit Pratishthan ; also available at Chowkhamba Vidyabhawan, 2002)
Classical work on Indic philosophy.